Rare Primary Pulmonary Marginal Zone Lymphoma Presenting with Incidental Pulmonary Nodules - Saad Ullah; Mirza Ali; Mingchen Song (Case Reports in Pulmonology)
Pulmonary malignancies carry a significant morbidity and mortality and are one of the leading causes of cancer-related deaths worldwide. Primary pulmonary lymphoma is a rare malignancy which should be considered in the differential of solitary pulmonary nodule or lung mass especially in a low-risk patient presenting with constitutional symptoms. Here, we describe a case of an elderly male who presented to our clinic with incidental pulmonary nodules and subsequent workup revealed low grade B cell non-Hodgkin's lymphoma consistent with diagnosis of primary pulmonary marginal zone lymphoma.